Mof-74 / melamine sponge derived composites, methods of making and using the same
Patent Information
- Application Number
- CN202311233071.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-22
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2043-09-22
AI Technical Summary
近年来,介孔碳材料被广泛应用于电磁波吸收材料的研究和制备,但其单一的介电损耗机制使其在强损耗、宽频带吸波材料的研究方面具有局限性,北京科技大学曹文斌教授制备了蠕虫状SiC纳米线并用于电磁波吸收,其单一的介电损耗使其阻抗匹配性差、电磁波损耗能力弱,导致其电磁波吸收能力差,仅实现了-35.2 dB的反射损耗以及1.8 GHz的有效吸波带宽
1、本发明通过合理的组成、界面调控与多层次结构设计,将三聚氰胺海绵与MOF-74相结合,构筑出兼具轻质、宽带、强吸收的结构功能一体化吸波材料,首次使用由2,5-二羟基对苯二甲酸作为有机配体的MOFs结构(MOF-74),并与不同磁性金属成分(Co、CoNi、FeCoNi)配位,制备了MOF-74/三聚氰胺海绵衍生的电磁波吸收材料。三聚氰胺海绵热解后产生了大量缺陷结构,引发了丰富的偶极极化,三聚氰胺海绵的多孔结构促使电磁波在材料内部进行多重反射,实现了多重损耗。材料表面的磁性粒子可以引发磁损耗,同时调节了阻抗匹配。利用三聚氰胺海绵和MOF-74复合制备磁性过渡金属掺杂碳复合材料,得到了吸波性能高效的吸波材料。
Smart Images

Figure CN117285036B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electromagnetic wave absorbing materials technology, specifically relating to MOF-74 / melamine sponge-derived composite materials, their preparation methods, and applications. Background Technology
[0002] Research on electromagnetic wave absorbing materials is of paramount importance. Currently, electromagnetic wave absorbing materials are gradually developing towards matching thinness, light weight, wide effective absorption bandwidth, and strong reflection loss.
[0003] Electromagnetic wave loss mechanisms include dielectric loss, conduction loss, and magnetic loss. Therefore, absorbing materials can be classified into conduction loss type, dielectric loss type, and magnetic loss type absorbing materials. Conduction loss type absorbing materials include carbon nanotubes, carbon nanofibers, carbon nanowires, graphene, and polycarbonate, which possess excellent conduction loss capabilities and low density, but their electromagnetic wave absorption performance is relatively weak. Dielectric loss type absorbing materials, such as inorganic semiconductors and ceramics, have excellent thermal stability and oxidation resistance, but their absorption capacity is lower than that of carbon-based materials. Magnetic loss type absorbing materials include magnetic metals or magnetic metal oxides. Their magnetic loss mechanism helps to adjust the impedance matching of the material, especially at low frequencies, but their high density limits the application of magnetic loss type absorbing materials.
[0004] Current research indicates that combining magnetic materials with carbon-based materials can create high-performance magnetoelectric composite loss absorbing materials, significantly improving their electromagnetic wave loss capability. In recent years, mesoporous carbon materials have been widely used in the research and preparation of electromagnetic wave absorbing materials. However, their single dielectric loss mechanism limits their application in high-loss, wide-bandwidth absorbing materials. Professor Cao Wenbin of Beijing University of Science and Technology prepared worm-like SiC nanowires for electromagnetic wave absorption; however, their single dielectric loss resulted in poor impedance matching and weak electromagnetic wave loss capability, leading to poor electromagnetic wave absorption, achieving only a reflection loss of -35.2 dB and an effective absorption bandwidth of 1.8 GHz. However, combining mesoporous carbon materials with magnetic metal materials introduces a magnetic loss mechanism, which can significantly adjust impedance matching and enhance electromagnetic wave loss capability. However, current technologies only achieve high reflection loss and a wide effective absorption bandwidth with high matching thicknesses for composite materials of mesoporous carbon and magnetic metals, making it impossible to achieve both lightweight and high performance in practical applications, thus limiting the application of absorbing materials.
[0005] Based on the above-mentioned technical deficiencies, this invention designs a novel and efficient MOF-derived metal-doped porous carbon microwave absorbing material, providing a new strategy for developing high-performance and lightweight electromagnetic wave absorbing materials. Summary of the Invention
[0006] To address the aforementioned technical shortcomings, this invention provides a MOF-74 / melamine sponge-derived composite material, its preparation method, and its applications. This invention addresses the challenges faced in the field of electromagnetic wave absorption by preparing a MOF-74 / melamine sponge-derived composite material. The dielectric constant and impedance matching of the composite material are adjusted by utilizing the tunable composition and microstructure of MOF-74. After pyrolysis, the unique structure of the melamine sponge and the Co, CoNi, and FeCoNi magnetic particles grown on its surface generate multiple losses in electromagnetic waves, enabling the absorbing material to achieve high reflection loss and a wide effective absorption bandwidth with a relatively low matching thickness.
[0007] To achieve the above objectives, the technical solution of the present invention is as follows: The preparation method of MOF-74 / melamine sponge-derived composite material includes the following steps: (1) Preparation of MOF-74 / melamine sponge precursor: Melamine cotton, metal salt and 2,5-dihydroxyterephthalic acid were dispersed in a solvent to obtain a mixed solution. The mixed solution was poured into a reaction vessel lined with melamine sponge and subjected to hydrothermal reaction. Then it was dried in a vacuum drying oven until all the solvent evaporated to obtain MOF-74 / melamine sponge precursor. (2) Preparation of MOF-74 / melamine sponge-derived composite material: The MOF-74 / melamine sponge precursor from step (1) was carbonized in an inert atmosphere to obtain a MOF-74 / melamine sponge-derived composite material.
[0008] Preferably, the metal salt in step (1) is selected from one or more of cobalt salts, nickel salts, and iron salts.
[0009] Preferably, the cobalt salt is selected from cobalt nitrate hexahydrate or cobalt chloride hexahydrate, the nickel salt is selected from nickel nitrate hexahydrate or nickel chloride hexahydrate, and the iron salt is selected from ferric nitrate nonahydrate or ferric chloride hexahydrate.
[0010] Preferably, the molar ratio of melamine cotton, metal salt and 2,5-dihydroxyterephthalic acid in step (1) is 4:1:0.8-1.
[0011] Preferably, the solvent in step (1) is composed of N,N'-dimethylformamide, deionized water and anhydrous ethanol in a volume ratio of 15-17:1:1.
[0012] Preferably, the hydrothermal reaction conditions in step (1) are: hydrothermal reaction at 130-140℃ for 24-26 hours.
[0013] Preferably, the carbonization method in step (2) is: setting the heating rate to 3-5℃ / min and holding at 750-850℃ for 2-2.5h.
[0014] The present invention also protects the MOF-74 / melamine sponge-derived composite material prepared by the above preparation method, wherein the MOF-74 / melamine sponge-derived composite material has a porous structure and magnetic components, and has an electromagnetic coordination effect that helps to dissipate electromagnetic waves.
[0015] This invention also protects the application of MOF-74 / melamine sponge-derived composite material in the preparation of electromagnetic wave absorbing materials, wherein the method of application is: mixing MOF-74 / melamine sponge-derived composite material with a polymer matrix to prepare an electromagnetic wave absorbing coating; The polymer matrix includes polyurethane and epoxy resin.
[0016] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. This invention, through rational composition, interface control, and multi-level structural design, combines melamine sponge with MOF-74 to construct an integrated microwave absorbing material with lightweight, wide bandwidth, and strong absorption capabilities. It is the first to use a MOF structure (MOF-74) with 2,5-dihydroxyterephthalic acid as the organic ligand, and coordinates it with different magnetic metal components (Co, CoNi, FeCoNi) to prepare an electromagnetic wave absorbing material derived from MOF-74 / melamine sponge. The pyrolysis of melamine sponge generates numerous defect structures, inducing abundant dipole polarization. The porous structure of the melamine sponge promotes multiple reflections of electromagnetic waves within the material, resulting in multiple losses. Magnetic particles on the material surface can induce magnetic loss and simultaneously adjust impedance matching. By using melamine sponge and MOF-74 to prepare a magnetic transition metal-doped carbon composite material, a microwave absorbing material with high absorption performance was obtained.
[0017] 2. This invention uses melamine sponge as a template and combines it with MOF-74 containing different magnetic metals. The research provides rich experience for in-depth exploration of the composition control of transition metal doped hierarchical carbon composite materials.
[0018] 3. This invention designs a MOF-74 / melamine sponge-derived composite material with multiple electromagnetic wave loss mechanisms. At a matching thickness of 2.67 mm, its reflection loss can reach a maximum of -80.65 dB, and at a matching thickness of 2.14 mm, the effective absorption bandwidth reaches 5.28 GHz. Its excellent electromagnetic wave absorption capability also stems from the interaction between the carbon matrix and magnetic particles, specifically the following two points: (1) The magnetic metal particles generated on the surface of the carbon matrix provide a magnetic loss mechanism, which adjusts the impedance matching of the absorbing material and forms an interface polarization with the carbon matrix, promoting the loss of electromagnetic waves; (2) The carbon matrix and magnetic particles provide an electromagnetically synergistic electromagnetic wave loss mechanism, which further improves the impedance matching of the absorbing material and enhances the electromagnetic wave absorption and loss capability. Attached Figure Description
[0019] Figure 1 Figures (a) and (b) are scanning electron microscope images of CoNi / N / C at different magnifications, (c) is a transmission electron microscope image of CoNi / N / C, (d) and (e) are high-resolution transmission electron microscope images of CoNi / N / C, and (f) is a selected area electron diffraction pattern of CoNi / N / C. Figure 2 Figure (a) shows the XRD patterns of Co / N / C, CoNi / N / C and FeCoNi / N / C, and Figure (b) shows the Raman patterns of Co / N / C, CoNi / N / C and FeCoNi / N / C. Figure 3 The figures are XPS spectra of CoNi / N / C; where (a) is the full spectrum, (b) is the C1s spectrum, (c) is the N1s spectrum, (d) is the Co2p spectrum, and (e) is the Ni2p spectrum. Figure 4 The figures show the electromagnetic parameters of Co / N / C, CoNi / N / C, and FeCoNi / N / C; where (a) is the real part of the dielectric constant, (b) is the imaginary part of the dielectric constant, (c) is the tangent of the dielectric loss angle, (d) is the real part of the permeability, (e) is the imaginary part of the permeability, and (f) is the tangent of the magnetic loss angle. Figure 5 In the figure, (a) is a 3D diagram of the microwave absorption performance of Co / N / C, (b) is a contour plot of the microwave absorption performance of Co / N / C, (c) is a 3D diagram of the microwave absorption performance of CoNi / N / C, (d) is a contour plot of the microwave absorption performance of CoNi / N / C, (e) is a 3D diagram of the microwave absorption performance of FeCoNi / N / C, and (f) is a contour plot of the microwave absorption performance of FeCoNi / N / C. Figure 6 The reflection loss diagram of Co / N / C obtained in Example 3; Figure 7 The reflection loss diagram of CoNi / N / C prepared in Example 1 is shown. Figure 8 The image shows the reflection loss of FeCoNi / N / C prepared in Example 2. Detailed Implementation
[0020] The specific embodiments of the present invention are described in detail below, but it should be understood that the scope of protection of the present invention is not limited to the specific embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention. Unless otherwise specified, the experimental methods described in the embodiments of the present invention are conventional methods.
[0021] Unless otherwise specified, the experimental and testing methods described below are conventional methods; unless otherwise specified, the reagents and raw materials described below are commercially available.
[0022] Example 1 The preparation method of MOF-74 / melamine sponge-derived composite material includes the following steps: (1) Preparation of MOF-74 / melamine sponge precursor: Melamine sponge was cut into cubes measuring 3 cm × 1 cm × 1 cm and placed in a flask. Then, 0.47 g of cobalt nitrate hexahydrate, 0.23 g of nickel nitrate hexahydrate, and 0.71 g of 2,5-dihydroxyterephthalic acid were added to a beaker containing melamine sponge. Solvent was then added and the mixture was stirred until homogeneous, resulting in a mixed solution. This mixed solution was poured into a reaction vessel containing melamine sponge and subjected to hydrothermal reaction at 135 °C for 24 h. The resulting product was then placed in a vacuum drying oven and dried at 70 °C for 24 h until all the solvent evaporated, yielding the CoNi-MOF-74 / melamine sponge precursor. The solvent consists of N,N-dimethylformamide, deionized water, and anhydrous ethanol, with a volume ratio of 15:1:1. (2) Preparation of CoNi / N / C (M=Co, CoNi, FeCoNi) composite materials: The CoNi-MOF-74 / melamine sponge precursor from step (1) was placed in a tube furnace and argon gas was introduced. The heating rate was set to 5℃ / min and held at 800℃ for 2.5h. After that, it was naturally cooled to room temperature. The resulting sample was named CoNi / N / C.
[0023] Example 2 The preparation method of MOF-74 / melamine sponge-derived composite material includes the following steps: (1) Preparation of MOF-74 / melamine sponge precursor: Melamine sponge was cut into cubes measuring 3 cm × 1 cm × 1 cm and placed in a flask. Then, 0.23 g of cobalt nitrate hexahydrate, 0.23 g of nickel nitrate hexahydrate, 0.32 g of ferric nitrate nonahydrate, and 0.71 g of 2,5-dihydroxyterephthalic acid were added to the beaker containing the melamine sponge. Solvent was then added and the mixture was stirred until homogeneous, resulting in a mixed solution. This mixed solution was poured into a reaction vessel containing melamine sponge and subjected to hydrothermal reaction at 135 °C for 24 h. The resulting product was then placed in a vacuum drying oven and dried at 70 °C for 24 h until all the solvent evaporated, yielding the FeCoNi-MOF-74 / melamine sponge precursor. The solvent consists of N,N-dimethylformamide, deionized water, and anhydrous ethanol, with a volume ratio of 15:1:1. (2) Preparation of FeCoNi / N / C (M=Co, CoNi, FeCoNi) composite materials: The FeCoNi-MOF-74 / melamine sponge precursor from step (1) was placed in a tube furnace and argon gas was introduced. The heating rate was set to 5℃ / min and held at 800℃ for 2.5h. After that, it was naturally cooled to room temperature. The resulting sample was named FeCoNi / N / C.
[0024] Example 3 The preparation method of MOF-74 / melamine sponge-derived composite material includes the following steps: (1) Preparation of MOF-74 / melamine sponge precursor: Melamine sponge was cut into cubes measuring 3 cm × 1 cm × 1 cm and placed in a flask. Then, 0.47 g of cobalt nitrate hexahydrate and 0.71 g of 2,5-dihydroxyterephthalic acid were added to a beaker containing melamine sponge. Solvent was then added and the mixture was stirred until homogeneous to obtain a mixed solution. This mixed solution was poured into a reaction vessel containing melamine sponge and hydrothermally reacted at 135 °C for 24 h. The resulting product was then placed in a vacuum drying oven and dried at 70 °C for 24 h until all the solvent evaporated, thus obtaining the Co-MOF-74 / melamine sponge precursor. The solvent consists of N,N-dimethylformamide, deionized water, and anhydrous ethanol, with a volume ratio of 15:1:1. (2) Preparation of Co / N / C (M=Co, CoNi, FeCoNi) composite materials: The Co-MOF-74 / melamine sponge precursor from step (1) was placed in a tube furnace and argon gas was introduced. The heating rate was set to 5℃ / min and held at 800℃ for 2.5h. After that, it was naturally cooled to room temperature. The resulting sample was named Co / N / C.
[0025] Example 4 The preparation method of MOF-74 / melamine sponge-derived composite material includes the following steps: (1) Preparation of MOF-74 / melamine sponge precursor: Melamine sponge was cut into cubes measuring 3 cm × 1 cm × 1 cm and placed in a flask. Then, 0.23 g of cobalt nitrate hexahydrate, 0.23 g of nickel nitrate hexahydrate, 0.32 g of ferric nitrate nonahydrate, and 0.71 g of 2,5-dihydroxyterephthalic acid were added to the beaker containing the melamine sponge. Solvent was then added and the mixture was stirred until homogeneous, resulting in a mixed solution. This mixed solution was poured into a reaction vessel containing melamine sponge and subjected to hydrothermal reaction at 130 °C for 26 h. The resulting product was then placed in a vacuum drying oven and dried at 75 °C for 25 h until all the solvent evaporated, yielding the FeCoNi-MOF-74 / melamine sponge precursor. The solvent consists of N,N-dimethylformamide, deionized water and anhydrous ethanol, with a volume ratio of 16:1:1. (2) Preparation of FeCoNi / N / C (M=Co, CoNi, FeCoNi) composite materials: The FeCoNi-MOF-74 / melamine sponge precursor from step (1) was placed in a tube furnace and argon gas was introduced. The heating rate was set to 4℃ / min, and the temperature was maintained at 750℃ for 2.5h. After that, it was naturally cooled to room temperature. The resulting sample was named FeCoNi / N / C.
[0026] Example 5 The preparation method of MOF-74 / melamine sponge-derived composite material includes the following steps: (1) Preparation of MOF-74 / melamine sponge precursor: Melamine sponge was cut into cubes measuring 3 cm × 1 cm × 1 cm and placed in a flask. Then, 0.23 g of cobalt nitrate hexahydrate, 0.23 g of nickel nitrate hexahydrate, 0.32 g of ferric nitrate nonahydrate, and 0.71 g of 2,5-dihydroxyterephthalic acid were added to the beaker containing the melamine sponge. Solvent was then added and the mixture was stirred until homogeneous, resulting in a mixed solution. This mixed solution was then poured into a reaction vessel containing melamine sponge and subjected to hydrothermal reaction at 140 °C for 25 h. The resulting product was then placed in a vacuum drying oven and dried at 70 °C for 26 h until all the solvent evaporated, yielding the FeCoNi-MOF-74 / melamine sponge precursor. The solvent consists of N,N-dimethylformamide, deionized water, and anhydrous ethanol, with a volume ratio of 17:1:1. (2) Preparation of FeCoNi / N / C (M=Co, CoNi, FeCoNi) composite materials: The FeCoNi-MOF-74 / melamine sponge precursor from step (1) was placed in a tube furnace and argon gas was introduced. The heating rate was set to 3℃ / min and held at 850℃ for 2h. After that, it was naturally cooled to room temperature. The resulting sample was named FeCoNi / N / C.
[0027] Examples 1-5 of this invention all yielded microwave absorbing materials that achieved high reflection loss and wide effective absorption bandwidth at relatively low matching thicknesses, with similar absorption performance. The MOF-74 / melamine sponge-derived composite materials prepared in Examples 1-3 are used as examples for further research. Specific research methods and results are shown below: Figure 1 The results show that magnetic metal particles were generated on the CoNi / N / C material obtained by pyrolysis. The generation of magnetic metal particles is beneficial for providing magnetic loss to the material and forming interfacial polarization with the carbon matrix, thereby improving the material's attenuation capability for electromagnetic waves. Furthermore, the magnetic metal particles can promote impedance matching of the material. High-resolution transmission electron microscopy and selected area electron diffraction patterns show that the (111) crystal plane of Co, the (400) crystal plane of NiCo2O4, and the (111) crystal plane of C have interplanar spacings of 0.204 nm, 0.201 nm, and 0.331 nm, respectively, indicating that graphitic carbon and the crystal structures of Co and NiCo2O4 were generated in the material.
[0028] Figure 2 The results show that the X-ray diffraction patterns of Co / N / C, CoNi / N / C, and FeCoNi / N / C composites are as follows: Figure 2As shown in (a), the crystal structure of the materials is characterized. All three composite materials exhibit diffraction peaks at 2θ = 26°, indicating the formation of graphitic carbon. For Co / N / C, CoNi / N / C, and FeCoNi / N / C, the diffraction peaks for Co appear at 2θ = 52.2° and 61.5°, indicating the formation of metallic Co. CoNi / N / C shows a diffraction peak for NiCo₂O₄ at 2θ = 53.1°, indicating that NiCo₂O₄ was formed after the pyrolysis of CoNi / N / C. FeCoNi / N / C shows a diffraction peak for NiFe₂O₄ at 2θ = 51.4°, indicating the presence of NiFe₂O₄. Figure 2 (b) Raman spectra of Co / N / C, CoNi / N / C, and FeCoNi / N / C. I D / I G The value gradually decreases, indicating that its degree of graphitization gradually increases.
[0029] Figure 3 The results show that five elements—C, N, O, Co, and Ni—are present in CoNi / N / C. The characteristic peaks in the C 1s spectrum indicate the presence of C-C, C-N, CO, and CO=C bonds. The N 1s spectrum demonstrates the presence of pyridine nitrogen, pyrrole nitrogen, and graphitic nitrogen. Furthermore, the Co 2p and Ni 2p spectra show the presence of Co... 2+ and Co 3+ and Ni 2+ and Ni 3+ The existence of.
[0030] Figure 4 The results show that, as a normal phenomenon for dielectrics, the real parts of the dielectric constants of Co / N / C, CoNi / N / C, and FeCoNi / N / C gradually decrease with increasing frequency. The imaginary part of the dielectric constant of FeCoNi / N / C shows a decreasing trend with increasing frequency, while the imaginary part curves of the dielectric constants of Co / N / C and CoNi / N / C exhibit resonance peaks, which are induced by polarization relaxation. Furthermore, this series of materials possesses low complex permeability parameters, indicating that magnetic loss has a relatively small impact on the electromagnetic wave absorption capability of these materials. Therefore, the contribution of dielectric loss plays a major role in the electromagnetic wave absorption performance of Co / N / C, CoNi / N / C, and FeCoNi / N / C.
[0031] Figures 5-8The results show that CoNi / N / C achieves a maximum reflection loss of -80.65 dB at a matching thickness of 2.67 mm, and an effective absorption bandwidth of 5.28 GHz at a matching thickness of 2.14 mm, indicating that CoNi / N / C exhibits excellent electromagnetic wave absorption performance. The reflection loss and effective absorption bandwidth of Co / N / C and FeCoNi / N / C are both lower than those of CoNi / N / C. This demonstrates that CoNi / N / C has the best absorption performance among the three samples, and that all materials in this series possess excellent absorption performance.
[0032] Obviously, those skilled in the art can make various modifications and variations to this invention without departing from its spirit and scope. Therefore, if these modifications and variations fall within the scope of the claims of this invention and their equivalents, this invention also intends to include these modifications and variations.
Claims
1. The application of the preparation method of MOF-74 / melamine sponge-derived composite material in the preparation of electromagnetic wave absorbing materials, characterized in that, Includes the following steps: (1) Preparation of MOF-74 / melamine sponge precursor: Melamine sponge, metal salt and 2,5-dihydroxyterephthalic acid were dispersed in a solvent to obtain a mixed solution. The mixed solution was poured into a reaction vessel lined with melamine sponge and subjected to hydrothermal reaction. Then it was dried until all the solvent evaporated to obtain MOF-74 / melamine sponge precursor. In step (1), the metal salts are cobalt salts and nickel salts; In step (1), the molar ratio of melamine sponge, metal salt and 2,5-dihydroxyterephthalic acid is 4:1:0.8-1. The conditions for the hydrothermal reaction in step (1) are: hydrothermal reaction at 130-140℃ for 24-26 hours; (2) Preparation of MOF-74 / melamine sponge-derived composite material: The MOF-74 / melamine sponge precursor from step (1) was carbonized in an inert atmosphere to obtain a MOF-74 / melamine sponge-derived composite material. The carbonization method in step (2) is as follows: set the heating rate to 3-5℃ / min and keep it at 750-850℃ for 2-2.5h.
2. The application of the preparation method of MOF-74 / melamine sponge-derived composite material according to claim 1 in the preparation of electromagnetic wave absorbing materials, characterized in that, The cobalt salt is selected from cobalt nitrate hexahydrate or cobalt chloride hexahydrate, and the nickel salt is selected from nickel nitrate hexahydrate or nickel chloride hexahydrate.
3. The application of the preparation method of MOF-74 / melamine sponge-derived composite material according to claim 1 in the preparation of electromagnetic wave absorbing materials, characterized in that, The solvent in step (1) consists of N,N'-dimethylformamide, deionized water and anhydrous ethanol in a volume ratio of 15-17:1:
1.
4. The application of the preparation method of MOF-74 / melamine sponge-derived composite material according to claim 1 in the preparation of electromagnetic wave absorbing materials, characterized in that, The method of application is as follows: mix MOF-74 / melamine sponge-derived composite material with a polymer matrix to prepare an electromagnetic wave absorbing coating.
5. The application of the preparation method of MOF-74 / melamine sponge-derived composite material according to claim 4 in the preparation of electromagnetic wave absorbing materials, characterized in that, The polymer matrix is polyurethane or epoxy resin.
Citation Information
Patent Citations
FeCoNi@C / carbon fiber aerogel composite absorbing material and preparation method thereof
CN110983492A
Melamine sponge-based nitrogen-doped CoO / Co / C composite material as well as preparation method and application thereof
CN116355588A
Cobalt-manganese-iron alloy-carbon composite wave-absorbing material as well as preparation method and application thereof
CN116583097A